A multicolor multiplex lateral flow assay for high-sensitivity analyte detection using persistent luminescent nanophosphors. Issue 3 (17th December 2019) - Danthanarayana, Adheesha N.; Finley, Erin; Vu, Binh; Kourentzi, Katerina; Willson, Richard C.; Brgoch, Jakoah
Abstract : Multicolor multiplex lateral flow assay using persistent luminescent nanophosphors as reporters. Abstract : Incorporating two persistent luminescent nanophosphors (PLNPs), green-emitting SrAl2 O4 :Eu 2+, Dy 3+ (SAO) and blue-emitting (Sr0.625 Ba0.375 )2 MgSi2 O7 :Eu 2+, Dy 3+ (SBMSO), in a single lateral flow assay (LFA) establishes a luminescence-based, multiplex point-of-need test capable of simultaneously detecting two different analytes in a single sample. The advantages of this system are the high sensitivity and photostability of PLNPs, while only requiring access to minimal hardware and a smartphone for signal detection. The PLNPs were obtained by first wet milling bulk synthesized phosphor powders, followed by fractionation using differential centrifugal sedimentation to obtain monodisperse nanoparticles. A modified Stöber process was then employed to encapsulate the nanoparticles in a water-stable silica shell followed by attaching antibodies to the particles' surfaces using reductive amination chemistry. The resulting PLNPs were incorporated in an LFA to concurrently detect two independent model analytes, prostate-specific antigen (PSA) and human chorionic gonadotropin (hCG). The multicolor-multiplex PLNP-based assays were finally imaged using a smartphone-based imaging system with excellent detection limits (0.1 ng mL −1 of PSA and 1 ng mL −1 of hCG) that are competitive with commercially available LFAs.